If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 31292e + -1(9) Multiply -1 * 9 y = 31292e + -9 Reorder the terms: y = -9 + 31292e Solving y = -9 + 31292e Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -9 + 31292e
| (x+7)-(x+3)= | | 180=(180-(2x+60))+(3x+10)+x | | y=31292e-(0.2x) | | 180=(-180+(2x+60))+(3x+10)+x | | (x+7)+(x+3)= | | 180=(-180+2x+60)+(3x+10)+x | | 180=2x+3x+-180+60+10 | | 5(x-2)+4(x+2)=14-4x | | 4+-9x=9x+-2 | | 6=3sqrt | | 8x=-4x+-3x | | -16(t^2+4t+5)=0 | | d=1/16*8^2 | | d=1/16*7^2 | | d=1/16*9^2 | | d=1/16*60^2 | | d=1/16*20^2 | | 180=78+y+1.5y | | -1(4+x)=14 | | 7(x-2)+2(x+1)=1-3x | | 11x-2y=18 | | (12x+3x+2)-(12x+5)=6x+11 | | 2(3*5)=6y | | x-3x+2x=-310 | | 2x^6-9x^5+10x^4-3x^3+10x^2+2=0 | | 7x+35=77 | | (8x*2+5x+4)-(8x*2+5)=8x+10 | | 180=-10-120+x-3x+2x | | (5x*2+6x-1)-(5x*2+8)=15 | | 310=-2x+2x | | x-.1x=231 | | 180=x-(3x+10)-(180-(2x+60)) |